2011
DOI: 10.1080/10810730.2010.546487
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Communication as an Indirect Pathway for the Effect of Antismoking Media Content on Smoking Cessation

Abstract: In the context of health campaigns, interpersonal communication can serve at least 2 functions: (a) to stimulate change through social interaction and (b) in a secondary diffusion process, to further disseminate message content. In a 3-wave prospective study of 1,079 smokers, the authors demonstrate that mass media messages (antismoking campaigns and news coverage relevant to smoking cessation) have an indirect effect on smoking cessation intention and behavior via interpersonal communication. Exposure to camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
108
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 28 publications
(15 reference statements)
15
108
1
1
Order By: Relevance
“…Yet despite the knowledge that interpersonal conversations about health can increase campaign reach, we know very little about what specifically influences people to talk about and share health information (Southwell & Yzer, 2009). Prior research has established important links between perceived health knowledge, attitudes, and behavioral Downloaded by [Georgetown University] at 10:35 22 August 2015 intentions (Freberg, 2013;Pecchioni & Sparks, 2007;Valente, Paredes, & Poppe, 1998). We also know people are barraged by health information and are increasingly deemed responsible for their own health care decisions (Brashers, Goldsmith, & Hsieh, 2002;Navarro & Wilkins, 2001).…”
Section: Please Scroll Down For Articlementioning
confidence: 94%
“…Yet despite the knowledge that interpersonal conversations about health can increase campaign reach, we know very little about what specifically influences people to talk about and share health information (Southwell & Yzer, 2009). Prior research has established important links between perceived health knowledge, attitudes, and behavioral Downloaded by [Georgetown University] at 10:35 22 August 2015 intentions (Freberg, 2013;Pecchioni & Sparks, 2007;Valente, Paredes, & Poppe, 1998). We also know people are barraged by health information and are increasingly deemed responsible for their own health care decisions (Brashers, Goldsmith, & Hsieh, 2002;Navarro & Wilkins, 2001).…”
Section: Please Scroll Down For Articlementioning
confidence: 94%
“…These levels of campaign intensity enable messages to be seen multiple times so they can be processed as intended and, thus, achieve population-wide influence. While research shows that part of the population-wide effect is generated by smokers quitting in direct response to such messages, another key effect is to increase community discussion [10] and to change broader social norms that reduce the social acceptability of smoking, leading to higher support for policy change and more social support and services to help smokers quit [11].Adding to this is Langley et al 's paper [5], which shows a decline in the demand for quitting information and assistance after the United Kingdom's anti-tobacco campaign funding was cut. This study underlines the importance of smokers being exposed to regular ongoing campaign activity to inform and remind them of the importance of quitting and to re-energize their desire to quit, so that they put quitting at the top of their priority list.…”
mentioning
confidence: 99%
“…These levels of campaign intensity enable messages to be seen multiple times so they can be processed as intended and, thus, achieve population-wide influence. While research shows that part of the population-wide effect is generated by smokers quitting in direct response to such messages, another key effect is to increase community discussion [10] and to change broader social norms that reduce the social acceptability of smoking, leading to higher support for policy change and more social support and services to help smokers quit [11].…”
mentioning
confidence: 99%
“…The majority of research indicates that interpersonal communication prompted by campaigns enhances knowledge, pro-attitudinal shifts, and positive behavior change (Chatterjee, Bhanot, Frank, Murphy, & Power, 2009;Dunlop, Wakefield, & Kashima, 2008;Southwell & Torres, 2006;van den Putte, Yzer, & Brunsting, 2005). Studies show that the mere presence of campaign-related conversation, regardless of its valence, shifts attitudes, intentions, and actual health behaviors toward a campaign's advocated position (Durkin & Wakefield, 2006;Valente & Saba, 1998;van den Putte, Yzer, Southwell, de Bruijn, & Willemsen, 2011). One study found that conversations prompted by a health campaign still led to positive health outcomes even when those engaging in the conversations had negative reactions to the campaign, suggesting that talk has a neutralizing effect on negative perceptions toward campaign content (Hafstad & Aarø, 1997).…”
Section: Exposure To and Interpersonal Communication About Health Cammentioning
confidence: 95%